Rappresentare la città degli anni Cinquanta: una questione di stile - Martinengo, Margherita (Status Quaestionis, 2025)
The article analyzes the ways in which the city, the center of the dynamics of capitalist and industrialized society, is represented by Calvino in works referable to the project Cronache degli anni Cinquanta. The strategies with which urban space is depicted offer a privileged point of entry to define the style of the production examined; on the one hand, they reflect the still-living attraction toward the composition of works that represent and confront historical-social reality, and on the other hand, they are the result of a new formal research, marked by an awareness of the obsolescence of a certain type of realistic novel.